1965
DOI: 10.1016/0021-9681(65)90080-9
|View full text |Cite
|
Sign up to set email alerts
|

Hand deformities in Parkinsonism

Abstract: IN HIS original and classic description of the disease that now bears his name, PARKINSON [l] noted the progressive muscular rigidity, the characteristic pill-rolling tremor, the stooping posture, the shufEing gait and the akinesia that characterize this condition. He did not, however, describe the digital deformities that are the subject of this paper. C~GCESHALL [2] states that "Charcot first pointed out the resemblance between Parkinsonism and rheumatoid arthritis, especially the similar deformities of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1968
1968
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The exact incidence of limb contractures in PD is unclear, perhaps because it is rare and often unrecognised. In a series of 86 parkinsonian patients Reynolds et al [19] in 1965 found that 34 (40%) had some deformity in the hands. These deformities were more frequent among those with post-encephalitic parkinsonism (71%) than without (24%).…”
Section: Discussionmentioning
confidence: 97%
“…The exact incidence of limb contractures in PD is unclear, perhaps because it is rare and often unrecognised. In a series of 86 parkinsonian patients Reynolds et al [19] in 1965 found that 34 (40%) had some deformity in the hands. These deformities were more frequent among those with post-encephalitic parkinsonism (71%) than without (24%).…”
Section: Discussionmentioning
confidence: 97%
“…A striatal hand has been described in 8.4% and striatal foot occurred in 5.9% of advanced-stage PD patients in one series [2]. The incidence of hand deformity in the pre-levodopa era was probably much higher, reaching 24% in one study [12]. Striatal abnormalities are more frequent in multiple system atrophy, where they have been described in 26.3% of individuals [2].…”
Section: Striatal Hand and Footmentioning
confidence: 98%
“…Striatal abnormalities are more frequent in multiple system atrophy, where they have been described in 26.3% of individuals [2]. Historically, the occurrence of Parkinson' DIP, distal interphalangeal joints striatal hand was particularly high in post-encephalitic parkinsonism, where 71% of patients developed such deformities in one series [12]. Striatal hand is characterized by flexion of the distal interphalangeal (DIP) joints, extension of the proximal interphalangeal (PIP) joints with flexion of the metacarpophalangeal (MCP) joints, fifth digit abduction, ulnar wrist deviation, and occasionally tight fist clenching [2,12,13].…”
Section: Striatal Hand and Footmentioning
confidence: 99%
See 2 more Smart Citations